Penambahan Kayu Manis Dan Gula Merah Terhadap Kadar Vitamin C Dan Ic50 Dalam Jus Jambu Biji Merah - Wijaya Putra, Anak Agung Ngurah Dwi Ariesta; Sintyadewi, Putu Rima (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
Indonesia as a tropical country has various kinds of fruit varieties. One of the famous fruits in Indonesia is guava. Guava fruit is popular with the public because it has a sweet taste. Ripe guava flesh can be processed into processed products such as jelly, jam, guava flour, fruit salad, fruit soup, chips, fruit juice, and fresh drinks. The benefits of guava fruit are many, such as being able to overcome several types of diseases such as diabetes, hypertension, and cancer. In addition, guava is also useful as an anti-bacterial, anti-fungal, anti-inflammatory, and can maintain skin health. Guava contains various vitamins and antioxidants that are beneficial for the body. The purpose of this study was to determine the content of vitamin C and antioxidant activity in guava juice added with cinnamon and brown sugar. This test uses 8 combinations of brown sugar and cinnamon treatments. The results showed that the best vitamin C content and antioxidant activity were found in the K2G0 treatment (4% cinnamon and 0% brown sugar) with a vitamin C content of 57,15 mg/100g and an IC 50 value of 39,08 ppm.